Podstawowe warianty pojęcia władzy w polskiej teorii państwa i prawa w okresie międzywojennym: [The fundamental variants of the notion of authority in the Polish theory of state and law between the wars] (Studia Prawnicze / The Legal Studies, 1986)
In the article an overall opinion is presented about the problem of the social authority in the Polish theory of state and law between the wars, taking into account in particular philosophical premises of opinions expressed at that time. The analysis of the conception of the social authority formulated in the writtings of the leading exponents of the contemporary legal theoretical thought in Poland, reveals the existence of two fundamental theoretical orientations in the understanding of the phenomenon of authority in society (psychologism and antipsychologism). Those orientations are based on different methodological and ontological assumptions. This fact affects decisevely the distincteveness of the for mulated conceptions of the social authority. In conclusion I indicate the ahistorism and the speculative character of the conceptions of authority at that time and their little usefullness in the kon\vledge of the real authority relations in society